Identificación de los problemas tributarios en las microempresas comerciales y su incidencia socioeconómica en el cantón La Maná, provincia de Cotopaxi 2017-2018. - Ojeda Ortíz, Ángela Guadalupe (2019)
Commercial micro companies assume an important role in the development of the country. They constitute the economic drivers and generators of employment sources, however, from the managerial point of view, these companies show a variety of behaviors in the tax area, administrative, marketing and management control. Despite the efforts that commercial micro companies or formal capital businesses are limited to be sustained in the market, many of them succumb to the aggressive competition of the environment, lack of financial resources that improve their assets or the economic effect of the country. Those aspects have made possible to visualize that in a small or large extent, fiscal tax processes are not known or are not implemented, or in fact they are executed in an inadequate manner. This situation limits the actions of the revenue or tax control agencies in their collection process. Values that affect negatively the economic and social retribution through the local budget. The study provides advices on the importance and application of tax processes in commercial micro companies for socioeconomic development in the municipality of La Maná canton by starting on the identification of the problem in which it is immersed according to the accomplishment of the principles of Internal Revenue Service in order to create competitive and self-sustaining entities. This is a non-experimental field investigation, but a descriptive-analytical one which starts on the diagnosis of the commercial micro companies of La Maná canton where tax documents, administrative processes, and accounting systems will be analyzed. The obtained results in the managerial area of the companies aimed to provide tax knowledge to micro businessmen, businesswomen, and employees of the area, so influencing positively on the socioeconomic development of the inhabitants of the zone.